Rheumatological involvements in inflammatory bowel diseases: Review - Ulusoy, Hasan; Akgöl, Gürkan; Kamanli, Ayhan (My University, 2010)
Inflammatory bowel diseases are systemic inflammatory diseases of unknown etiology that primarily affect the gastrointestinal system. A variety of clinical findings may arise outside of the gastrointestinal system in these diseases which may be seen in two different types to be ulcerative colitis and Crohn disease. These findings are termed extraintestinal involvements. The organs most commonly affected are peripheral and axial joints, skin, eyes, lungs and hepatobiliary tract, although nearly every organ may be affected. To day, the pathogenesis of extraintestinal involvements is not completely understood. Some of these are clearly related to bowel disease activity (i.e., erythema nodosum, peripheral arthritis), whereas others occur independently (i.e., pyoderma gangrenosum, axial arthritis, üveitis). Peripheral arthritis is usually oligoarticular and asymmetric, and may occur in a migratory pattern in some patients. The joints most commonly affected are knee, ankle, elbow, wrist and metatarsophalangeal joints. The arthritis is typically nonerosive, occurring in intermittent attacks lasting up to 12 weeks. There is no association between peripheral arthritis and HLA-B27. The axial pattern of arthritis is indistinguishable clinically and radiographically from primary ankylosing spondylitis. Unlike the peripheral arthritis, axial involvement is related to HLA-B27. Erythema nodosum tends to mirror the activity of the underlying bowel disease. Pyoderma gangrenosum is painful deep skin ulcerations and is less common. Acute anterior üveitis can be seen in up to 10% of patients with inflammatory bowel diseases. This review will focus on the rheumatological involvements seen in inflammatory bowel diseases. Copyright © 2010 by Türk Tibbi Rehabilitasyon Kurumu Derne?i.
İnflamatuvar ba?irsak hastaliklarinda romatolojik tutulumlar
Keywords: Crohn disease; Inflammatory bowel diseases; Ulcerative colitis